Annual report 1997 of the CGIAR System-wide Genetic Resources Programme - International Plant Genetic Resources Institute; CGIAR Systemwide Genetic Resources Programme (1998)
SGRP publishes every year a report providing a detailed overview of its activities. This report provides information on activities carried out in 1997.